Local c-di-GMP Signaling in the Control of Synthesis of the E. coli Biofilm Exopolysaccharide pEtN-Cellulose. Issue 16 (24th July 2020) - Richter, Anja M.; Possling, Alexandra; Malysheva, Nadezhda; Yousef, Kaveh P.; Herbst, Susanne; von Kleist, Max; Hengge, Regine
Abstract: In many bacteria, the biofilm-promoting second messenger c-di-GMP is produced and degraded by multiple diguanylate cyclases (DGC) and phosphodiesterases (PDE), respectively. High target specificity of some of these enzymes has led to theoretical concepts of "local" c-di-GMP signaling. In Escherichia coli K-12, which has 12 DGCs and 13 PDEs, a single DGC, DgcC, is specifically required for the biosynthesis of the biofilm exopolysaccharide pEtN-cellulose without affecting the cellular c-di-GMP pool, but the mechanistic basis of this target specificity has remained obscure. DGC activity of membrane-associated DgcC, which is demonstrated in vitro in nanodiscs, is shown to be necessary and sufficient to specifically activate cellulose biosynthesis in vivo . DgcC and a particular PDE, PdeK (encoded right next to the cellulose operon), directly interact with cellulose synthase subunit BcsB and with each other, thus establishing physical proximity between cellulose synthase and a local source and sink of c-di-GMP. This arrangement provides a localized, yet open source of c-di-GMP right next to cellulose synthase subunit BcsA, which needs allosteric activation by c-di-GMP. Through mathematical modeling and simulation, we demonstrate that BcsA binding from the low cytosolic c-di-GMP pool in E. coli is negligible, whereas a single c-di-GMP molecule that is produced and released in direct proximity to cellulose synthase increases the probability of c-di-GMP binding to BcsA several hundred-fold. This local c-di-GMP signaling could provide a blueprint for target-specific second messenger signaling also in other bacteria where multiple second messenger producing and degrading enzymes exist. Graphical abstract: Unlabelled Image Highlights: The diguanylate cyclase DgcC specifically activates cellulose synthase in E. coli, without affecting the low cellular c-di-GMP pool and despite the presence of several other active diguanylate cyclases. DgcC and a specific phosphodiesterase, PdeK, directly interact with the cellulose synthase complex. DgcC and PdeK operate as a local c-di-GMP source and sink, respectively, right next to the c-di-GMP-binding cellulose synthase subunit BcsA in an open, non-compartmentalized system. Mathematical modeling and simulation shows that this co-localization strongly increases the probability of c-di-GMP binding to BcsA and allows efficient signaling.